Single Reinforced Concrete Design of Simple Beam with Simple Formulation Method - Nia Dwi Puspitasari; Achmad Dzulfiqar Alfiansyah (Nusantara Science and Technology Proceedings, 2022)
A quick and practical method of designing a single-layer reinforced concrete beam will be analyzed. This article provides a new simple formulation to design simple beam-reinforced concrete. The dimension and reinforcement ratio can be generated by using the formulation. The variables that must be known at using the formulation are the concrete strength (f`c), the ultimate uniform load (qu), the yield strength of steel (fy), and the span length of the simple beam (L). There are two main parameters obtained from the formulation including the cross-sectional dimensions (W and H) and reinforcement ratios (?). Moreover, the required diameter and amount of steel reinforcement can be converted from the result. The beam dimensions and reinforcement ratio results obtained from this design method are verified by mathematical calculations based on the SNI 03-2847-2019. Designing a single-layer reinforced concrete beam using the simple formulation method provides high precision.